Taboo in Sasak Language Spoken in Kopang Rembiga Village - Fitriani Lestari; Budasi, I Gede; Dewi, Kadek Sintya (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
In order to avoid the extinction of Sasak Language, it is important for young generation of Sasak to maintain the existence of the language spoken in Kopang Rembiga Village. The objectives of this study are; to find out taboo words, taboo forms, and their references. The researchers were the main instruments in this study and the other additional instrument was an interview guide. The data collection technique was in-depth interview. Three types of data in the study were analyzed as follows: for taboo words were analyzed descriptively based on 3 domains in Tri Hita Karana concept, the forms of taboo words were analyzed using the theory of Frazer (1955) and Montagu (1973), and the references of taboo words were analyzed using the theory suggested by Laksana (2009). The results of the study are as follows: 1) there were 31 taboo words spoken in this village connecting with Tri Hita Karana concepts. The concepts consist to 3 domains of Parahyangan (living harmony with God); 1 word, Pawongan (living harmony with people); 22 words, and Palemahan (living harmony with nature); 8 words. 2) there are 23 taboo forms included in the taboo on names and words and also there are 8 taboo forms included to taboo on swearing words. 3) from the 31 words, there are 13 references of related to; parents name, animal name, god’s name, people name, peo6ple name who died, name of relatives, mentioning genitals, sexual activity, specific profession, bodily function, wisdom of ruler, nature, illness, name of spirits, personal pronouns, and specific activity.